2013
DOI: 10.1111/cts.12062
|View full text |Cite
|
Sign up to set email alerts
|

Summer Research Training for Medical Students: Impact on Research Self‐Efficacy

Abstract: There is a well documented shortage of physician researchers, and numerous training programs have been launched to facilitate development of new physician scientists. Short-term research training programs are the most practical form of research exposure for most medical students, and the summer between their first and second years of medical school is generally the longest period they can devote solely to research. The goal of short-term training programs is to whet the students’ appetite for research and spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 8 publications
2
43
0
1
Order By: Relevance
“…The new research tool had total scores related to the full RTE-questionnaire at .96 with internal consistency reliability at .88 approximately. 2) research outcome expectations (ROE) equipped with the Research Outcome Expectations Questions (ROEQ) by Bieschke (2000) having indicator of 1 aspect (8 items) with reliability at .90 3) research self-efficacy (RSE) was used research tools referred to the study of Black et al (2013) with 3 aspects indicator which were 1) research methodology and communication (6 items) 2) regulatory and organization-level aspect, and 3) interpersonal aspect with reliability of each aspect at .85 -.90 approximately. And 4) research interest (RI) equipped with the tool according to the study of van der Westhuizen (2015) as measurement for attitude toward research of students in graduate schools, in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…The new research tool had total scores related to the full RTE-questionnaire at .96 with internal consistency reliability at .88 approximately. 2) research outcome expectations (ROE) equipped with the Research Outcome Expectations Questions (ROEQ) by Bieschke (2000) having indicator of 1 aspect (8 items) with reliability at .90 3) research self-efficacy (RSE) was used research tools referred to the study of Black et al (2013) with 3 aspects indicator which were 1) research methodology and communication (6 items) 2) regulatory and organization-level aspect, and 3) interpersonal aspect with reliability of each aspect at .85 -.90 approximately. And 4) research interest (RI) equipped with the tool according to the study of van der Westhuizen (2015) as measurement for attitude toward research of students in graduate schools, in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Eventually, it will be important to document whether intensive mentor training such as the program described in this paper or others 11 results in an increase in the likelihood that mentees will remain in academic research careers. Improvements in self-efficacy around research skills have been reported in early stage learners with designated training programs, 59,60 but the impact of mentorship training on mentee self-efficacy has not been assessed. This is particularly important for researchers from underrepresented backgrounds, in which attrition at each step of the pipeline is disproportionately higher than for non-minority academic researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The research activities which students undertake may be part of established research programs or as stand-alone projects (Black et al 2013;Boyd and Wesemann 2009;Halpain et al 2005;Houlden et al 2004;Schor et al 2005; O'Connor Grochowski et al 2007;Rosenthal et al 2009;Mullan et al 2014), with many students being supervised by academic staff or clinicians associated with a medical school.…”
Section: Demonstrate a Commitment To Excellence Evidence Based Practmentioning
confidence: 99%